Pendekatan Ketauladanan Perspektif Pendidikan Islam dalam Pembinaan Karakter Peserta Didik Sekolah Dasar - Syaifur Rohman; M. Choirul Muzaini (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2023)
This study aims to examine how the exemplary approach is implemented by the teacher in order to build the character of elementary school students and examine the obstacles and conveniences that the teacher passes in building the character of students. The research approach is qualitative with the case study method, the subject of this research is Ringin Sari Public Elementary School. Data collection techniques used interviews, observation, and documentation. The research results reveal that the efforts that have been made by the teacher in fostering the character of students are not only related to manners, association, and actions in everyday life. The teacher's example can also be seen in the spiritual development of students by intermediary filling the souls and minds of students with patient, responsible, impartial, trustworthy, and forgiving qualities, and all of these characteristics must be exemplified through the personality of the teacher council. The inhibiting factors experienced by teachers in character building are the lack of understanding of religion that students have and the influence of an unsupportive environment.